Faktor – Faktor yang Mempengaruhi Loyalitas Pelanggan pada Rumah Makan Gudeg Lumintu di Kabupaten Jember - Ayuni, Candra Herdiana Indah Tiara; Ambarkahi, Ratih Puspitorini Yekti; Gemaputri, Ariesia Ayuning; Wiguna, Ardhitya Alam (Politeknik Negeri Jember, 2023)
In current conditions, competition in the restaurant business in Jember Regency is very tight. One of them is the Gudeg Lumintu restaurant in Jember district. In facing this competition, companies must have a strategy to gain loyalty from their customers through brand image, product quality and good service quality. This research aims to analyze (1) the influence of brand image, product quality and service quality on customer loyalty at Gudeg Lumintu Restaurant in Jember Regency simultaneously or partially, (2) variables that have a dominant influence on customer loyalty at Gudeg Lumintu Restaurant. Data was taken directly from respondents using a survey method via questionnaires. The sampling technique used was incidental sampling with a sample size of 40 respondents. The data analysis techniques used are multiple linear regression analysis, coefficient of determination analysis, F test and t test. The results of data analysis using SPSS 23 software show that (1) simultaneously, brand image variables (X1), product quality (X2) and service quality (X3) have a significant effect on customer loyalty (Y), (2) partially, image variables brand (X1) and product quality variables (X2) have a significant effect on customer loyalty (Y), while the service quality variable (X3) has an insignificant effect on customer loyalty (Y), (3) the variable has a dominant effect on customer loyalty (Y ) is the product quality (X2).